Bad object 2.0: Games and gamers - Steve Anderson (G|A|M|E The Italian Journal of Game Studies, 2015)
This is not a history project. Nor is it about video games and the people who play them. Instead, this project focuses on the cultural discourse surrounding digital games as they have been refracted by the lenses of American film and television. This study considers a broad cross-section of Hollywood’s depictions of games, tracing their evolution from objects of fascination and technological possibility in the 1970s and 1980s to catalysts for antisocial behavior in the 1990s and 2000s. This evolution maps revealingly onto the changing economic circumstances of the games industry, describing a direct correlation between the economic viability of the industry and its critical depiction in Hollywood.